Analisa Bubble Welding pada Proses Pengelasan Material Termoplastik SAN AS Menggunakan Mesin Ultrasonic Welding - Fogot Endro Wibowo; Evyta Wismiana; Fauzhia Rahmasari; Dimas Adi Prasetyo (Jurnal Teknologi, 2022)
The main problem that occurs in most ultrasonic welding processes on thermoplastic SAN (AS) materials that use ultrasonic welding machines is the selection of inappropriate parameters. This will cause various defects in the product, one of which is bubble welding. One of the most influential parameters on the welding results is the frequency and current parameters. This is because this parameter has a fairly high level of sensitivity to the welding results. Therefore, the purpose of this study was to examine the effect of frequency and current on the product produced by welding on 5 different parameters using 10 available samples. To determine the effect of the parameters of the magnitude of the frequency and current, the inspection method is used. This method aims to visually test the quality of the welding results. Based on the test, the results were obtained that by using the parameters of the frequency magnitude of 8 - 14 Hz and current of 15 - 18 amperes can produce the best welding results.